Investigation of muscle fatigue of the archer’s during endurance shooting - Hamdan, Z. A; Ahmad, Z.; Johari, N. H. (Faculty of Mechanical and Automotive Engineering Technology, UMP, 2022)
Endurance of Drawing-Aim-Release (DAR) during the shooting process in archery will be causing the muscles to fatigue. Besides, the archer's inability to use the right muscles for DAR will lead to a muscle injury as well as dropping the performance. This study aims to monitor the localized muscle fatigue of an archer during the repetitive DAR and its effect to the archer’s performance. Wet electrode sensors were placed on the specific muscles that are heavily involved in DAR such as Muscle Extensor Digitorum (MED) on the archer's bow arm and the Supraspinatus muscle at the shoulder. In order to induce fatigue, the archer has shot 72 arrows continously in 2 rounds of set. The surface electromyography (sEMG) signals of the muscle contraction are recorded during the shooting for the post-processing analysis. Each score of the shooting was also recorded to correlate with the effect of muscle fatigue to the archer’s performance. The finding of this study is that the MED and Supraspinatus begin to fatigue toward the end of each shooting round. The Root Mean Square (RMS) and Median Frequency (MDF) values for both targeted muscles increased significantly during the 6th end compare to the 1st end. It is also found that there is no correlation between muscle fatigue on MED and Supraspinatus to the score obtained by the archer where the F value is lower than F-critical while Draw (1.9339), Aim (1.3754) and Release (0.6515) phases. In conclusion, this experiment benefits archers and coaches to identify which muscles are vigorously used during the DAR process and allows for precaution and prevention procedures.